2000
DOI: 10.1006/jcph.2000.6584
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Multilayered Particles from Scattering Data by a Clustering Method

Abstract: A multilayered particle is illuminated by plane acoustic or electromagnetic waves of one or several frequencies. We consider the inverse scattering problem for the identification of the layers and of the refraction coefficients of the scatterer in a non-Born region of scattering. Local deterministic and global probabilistic minimization methods are studied. A special Reduction Procedure is introduced to reduce the dimensionality of the minimization space. Deep's and the Multilevel Single-Linkage methods for gl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…The HSD method could be described as a variation of a genetic algorithm and a local search with reduction. In [6] two global search algorithms in combination with a special local search method were applied to the identification of piecewise-constant scatterers by acoustic type measurements. The Rinnooy Kan and Timmer's Multilevel Single-Linkage Method in a combination with a special Local Minimization Method has been applied to the identification of piecewise-constant spherically symmetric potentials by their phase shifts in [7].…”
Section: Global and Local Minimization Methodsmentioning
confidence: 99%
“…The HSD method could be described as a variation of a genetic algorithm and a local search with reduction. In [6] two global search algorithms in combination with a special local search method were applied to the identification of piecewise-constant scatterers by acoustic type measurements. The Rinnooy Kan and Timmer's Multilevel Single-Linkage Method in a combination with a special Local Minimization Method has been applied to the identification of piecewise-constant spherically symmetric potentials by their phase shifts in [7].…”
Section: Global and Local Minimization Methodsmentioning
confidence: 99%
“…However, since the sought potential may have fewer than M layers, we found that conducting searches in lower-dimensional subspaces of R 2M is essential for the local minimization phase. A variation of the following "reduction" procedure has also been found to be necessary in [6] for the search of small subsurface objects, and in [4] for the identification of multilayered scatterers.…”
Section: Global and Local Minimization Methodsmentioning
confidence: 99%
“…Such method needs a minimization routine for a one-dimensional minimization of Φ, which we do using a Bisection or a Golden Rule method. See [4] or [5] for a complete description. Now we can describe our Basic Local Minimization Method in R 2M , which is a modification of Powell's minimization method [2].…”
Section: Global and Local Minimization Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of problems arises in many areas of technology and medicine (see [4] and the references therein). We have investigated this type of problem by FEM/BEM techniques [3].…”
Section: Introductionmentioning
confidence: 99%